UTILIZATION OF USED GOODS AS A HOUSEHOLD WASTE STORAGE IN PPKS EMPLOYEE HOUSING COMPLEX MARIHAT SIANTAR SIMALUNGUN NORTH SUMATRA - Hadi Pandjaitan; Firdasari; Josep Lubis (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Used goods are a problem that we often face in everyday life. One of the main factors for the accumulation of used goods is household waste. The provision of trash cans modified in such a way can have a positive impact on employees who live in the PPKS Marihat housing complex. Sheltering used goods is one form of employee care for the environment in which he lives. In addition, it can facilitate its transportation, in which household waste has been properly collected in the trash bins that have been provided.